2021
DOI: 10.1002/ppul.25454
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax prevalence and mortality per gestational age in the newborn

Abstract: Objectives: Pneumothorax (PTX) in newborns is a life-threatening condition associated with high morbidity and mortality especially in premature infants. The frequency of PTX in neonates at different gestational ages (GA) and its impact on neonatal mortality have not been quantified. We aimed to determine: (1) the prevalence of PTX in neonates at different GA from ≤24 to ≥37 weeks, (2) the impact of PTX on mortality per GA, and (3) the impact of PTX on the length of stay (LOS) per GA.Methods: The national Kids'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…On the other hand, the effect of sALS on mortality was not significant at 27 weeks of gestation, which seems to be due to the low mortality rate at 27 weeks of GA in both groups. In the large cohort study mentioned above, [29] it was reported that the effect of pneumothorax on death increased until GA reached a peak at 29 to 32 weeks, which was later than the peak of our study, and decrease. This pattern was similar with our study, although the range of GA was wide and the GA groups were divided roughly into it, and the mortality rates of the infants born before 29 weeks were lower than our study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the effect of sALS on mortality was not significant at 27 weeks of gestation, which seems to be due to the low mortality rate at 27 weeks of GA in both groups. In the large cohort study mentioned above, [29] it was reported that the effect of pneumothorax on death increased until GA reached a peak at 29 to 32 weeks, which was later than the peak of our study, and decrease. This pattern was similar with our study, although the range of GA was wide and the GA groups were divided roughly into it, and the mortality rates of the infants born before 29 weeks were lower than our study.…”
Section: Discussioncontrasting
confidence: 52%
“…A previous study on preterm infants born at < 29 weeks GA showed similar results in terms of mortality rate due to pneumothorax. [ 7 ] A large cohort study using the National Kids Inpatient Database [ 29 ] reported that the mortality rate of infants born at ≥ 25 weeks GA was higher in infants with pneumothorax than in those without pneumothorax. However, infants born at < 25 weeks GA had lower mortality rates with pneumothorax than those without pneumothorax, and the authors explained this result with the possibility that the infant died before pneumothorax occurred.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts significantly with the data on the incidence of pneumothorax usually described in the literature to date. 1,4 Recently, Acun et al 5 reported a global prevalence of pneumothorax in newborns of 0.034%, but the range of incidences described is broad depending on the population and the methodology used. In preterm newborns, the incidence of pneumothorax can reach 9%-20%.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax can develop spontaneously in healthy newborns or as a complication of a respiratory disease, neonatal respiratory distress syndrome, or meconium aspiration syndrome, among others. A wide range of incidence rates of pneumothorax in term newborns have been described, with that range between 0.05% and 0.17% 1–5 . However, these estimates are limited only to symptomatic newborns admitted to the neonatal intensive care unit (NICU) and having a chest X‐ray diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation